Preliminary high-dose irradiation of the recipient and associated damage of bone marrow stromal compartment enables bone marrow stroma transplantation - Aleksei Bigildeev; Evgeny Bigildeev; Eugenia Bulygina; Svetlana Tsygankova; Mariia Gusakova; Olga Illarionova (Scientific Reports)
Abstract Transplantability of allogeneic mesenchymal stem cells (MSCs) as a stable engraftment and participation in physiological renewal of bone marrow (BM) stroma remains an open question. We hypothesized that a necessary condition for successful MSCs transplantation is the prior significant damage to the recipient’s BM stroma. To test this, BM derived from male B10 mice was injected intravenously into syngeneic female mice irradiated with 6.5 Gy and 13 Gy, and unirradiated individuals. We measured donor chimerism 30 days after irradiation in recipients’ bones by RQ-PCR and in BM CFU-Fs by ddPCR. The ratio of PCR signals from single-copy Y chromosome-linked Prssly gene and autosomal Gapdh gene was used to determine donor chimerism. None of the non-irradiated recipients had donor cells in the BM subpopulation under study. In the group of recipients irradiated at a dose of 6.5 Gy, donor cells were detected at 0.16% in BM of only one animal. Increasing the radiation dose resulted in a significant increase in donor chimerism among BM stromal cells: it was 11% and 14% in two survived animals of this group. Donor chimerism in the bones of unirradiated recipients was not observed in any of the 15 samples. It was detected in only 2/18 bones of recipients irradiated with 6.5 Gy (0.8% and 1%). The median donor chimerism in bones of recipients irradiated with 13 Gy was 15%. We conclude that the condition for successful engraftment of donor stromal progenitor cells is prior damage to the recipient’s BM stroma. Development of protocols of MSCs and HSCs co-transplantation, when full donor chimerism of hematopoietic and stromal tissue will be observed in recipient BM, is feasible. It will allow to increase the efficiency of therapy of malignant and other diseases of blood system, for which allogeneic BM transplantation is indicated, as well as patients with impaired stroma function such as osteogenesis imperfecta and congenital generalized lipodystrophy.